3D Finite Elements Modeling of the Interfacial Stresses Bone/Dental Implant - Effects of the Geometric ParameterS - GHOGGALI, S.; OUTTAS, T.; LATRECHE, S. (Journal of Biomimetics, Biomaterials and Biomedical EngineeringJournal of Biomimetics, Biomaterials and Biomedical Engineering, 2017)
A successful osseointegration involves the simultaneous optimization of the primary stability of the implant and the minimization of interfacial stresses bone - implant. In this context, the modeling of these stresses reports a great interest for researchers in last decades.The aim of this work is to study the effects of geometric parameters of a new model of titanium dental implant on the evolution of interfacial stresses bone /implant. For this, a dental implant of the second premolar in the lower jaw was considered, with different diameters, thread pitches and different thread forms. The profile of the interfacial stresses was presented for each case study, the results show a great similarity in the areas concerned, cortical bone, threaded region and cancellous bone, with the results obtained in the literature for other types of geometries.